SOSIALISASI MODEL PEMBELAJARAN KURIKULUM MERDEKA DI SDIT AULIA, MUARA BULIAN - Yantoro; Muhammad Sholeh (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
Based on the results of interviews with school principals and teachers, information was obtained that schools did not understand the independent curriculum learning model, schools had not registered as schools implementing IKM (implementation of independent curriculum) and were still at the independent learning stage. Based on these problems, a solution is needed in the form of activities or programs for training and socialization for school members through community service training activities conducted by PGSD lecturers regarding school drive programs that will provide solutions to the problems faced by school residents. The targets to be achieved through this training activity are: 1). Producing school members who have the ability and knowledge to grow the implementation of the independent curriculum learning model, and 2) There is consultative assistance.